Faktor – Faktor Yang Mempengaruhi Minat Investasi Generasi Z Mahasiswa STIE Surakarta Di Pasar Modal - Febby Rahmawati; Rosita Rosita (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to test whether social media, motivation, knowledge and benefits influence the investment interest of the Z generation of STIE Surakarta students in the capital market. This research uses a quantitative method, the population in this study is 287, the sampling technique of this study is using purosive sampling. with the criteria of 7th Semester STIE Surakarta Accounting Study Program students. The data was distributed through questionnaires distributed via whatsapp grub class or personal WhatsApp to 7 semester 7 accounting students STIE Surakarta Study Program and obtained 125 respondents. The data analysis technique used in this study used regression multiple linear through the SPSS 25 program. The results of this study indicate that social media and knowledge do not affect the investment interest of the STIE Surakarta generation of students in the capital market, while the motivational and benefit variables affect the investment interest of the next generation. z STIE Surakarta students in the fashion market. Therefore, the z generation must be interested in investing in the capital market in order to provide long-term support. This research can help the whole community, especially young people, to better understand and be interested in investing in the capital market.